Pediatric SARS-CoV-2 infection and development of anxiety and depression - Dun-Dery, Frederick; Xie, Jianling; Zemek, Roger; Winston, Kathleen; Burstein, Brett; Sabhaney, Vikram; Emsley, Jason; Gravel, Jocelyn; Kam, April; Mater, Ahmed; Beer, Darcy; Porter, Robert; et al. (Frontiers in Pediatrics, 2025)
ObjectiveIt remains unclear whether emerging mental health concerns in children infected with SARS-CoV-2 are a direct result of the infection or due to the indirect effects of the pandemic. Therefore, we sought to assess the frequency of new diagnoses of anxiety and/or depression among children diagnosed with and without SARS-CoV-2 infection who were tested in pediatric emergency departments.MethodsA prospective cohort study with 6- and 12-month follow-ups was conducted across 14 Canadian tertiary-care pediatric emergency departments of the Pediatric Emergency Research Canada (PERC) network. The study included children aged <18 years who were tested for SARS-CoV-2 infection between August 2020 and February 2022. The primary outcome was the diagnosis of anxiety and/or depression reported during follow-up. The surveys incorporated a modified version of the International Severe Acute Respiratory and Emerging Infection Consortium (ISARIC) Long-COVID Pediatric Questionnaire.ResultsAmong the participants who were eligible for 6- and 12-month follow-ups, 64.7% (268/414) of SARS-CoV-2-positive and 71.9% (743/1,033) of SARS-CoV-2-negative participants completed follow-up at these time points, respectively. The median age was 7.0 [inter-quartile range (IQR): 5.0–11.0] years, and 54.2% (548/1,011) were male. New diagnoses of anxiety and/or depression reported on either survey did not differ significantly between test-positive (4.1%, 11/268) and test-negative (2.8%; 21/743) participants [difference = 1.3% (95% CI: −1.3 to 4.2)]. There was a higher prevalence of new diagnoses of anxiety and/or depression among SARS-CoV-2-negative participants aged ≥12 years relative to those aged <12 years [8.7% (13/149) vs. 1.3% (8/594); difference = 7.4%; 95% CI of the difference = 3.0–12.5], but not among SARS-CoV-2-positive participants [4.4% (2/45) vs. 4.0% (9/223); difference = 0.4%; 95% CI of the difference = −5.6 to 9.4]. At 6 or 12 months, SARS-CoV-2-positive participants were more likely to experience confusion and/or lack of concentration, abdominal pain, and insomnia.ConclusionsAlthough no association was found between SARS-CoV-2 infection and new diagnoses of anxiety and/or depression, SARS-CoV-2-positive participants were more likely to experience confusion/lack of concentration, abdominal pain, and insomnia. This finding, in the context of an increased prevalence of new diagnoses of anxiety and depression, underscores the impacts of societal changes on the mental health of children. Our finding that some non-specific symptoms were more frequently reported by SARS-CoV-2-positive participants emphasizes the need for further investigation of the underlying pathophysiologic mechanisms.